2021
DOI: 10.3390/ijerph18020702
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy and the Use of Technology on Older Adult Fall Prevention: A Scoping Review

Abstract: Introduction: Falls are the second leading cause of accidental or non-intentional deaths worldwide and are the most common problem as people age. The primary purpose of addressing falls is to detect, prevent, treat, and reduce their incidence and consequences. Previous studies identified that multifactorial programs, an interprofessional team, and assistive technology are required to address falls in older adults effectively. Accordingly, the research question is as follows: what are the scope, type of studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
(91 reference statements)
0
8
0
7
Order By: Relevance
“…Among the findings on the occupational therapy process, two types of interventions stand out with different characteristics regarding the professional's possibilities for action, namely: multicomponent intervention and single-component intervention. Single-component interventions are generally associated with one element, which may be: home safety assessment and modification, fall prevention education, or an exercise program (Miranda-Duro et al, 2021). Multicomponent interventions consist of individualized and comprehensive assessment, home modifications, home visits, educational components to prevent falls and functional training for balance, strength and mobility (Stark et al, 2017a;Blaylock & Vogtle, 2017;Miranda-Duro et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Among the findings on the occupational therapy process, two types of interventions stand out with different characteristics regarding the professional's possibilities for action, namely: multicomponent intervention and single-component intervention. Single-component interventions are generally associated with one element, which may be: home safety assessment and modification, fall prevention education, or an exercise program (Miranda-Duro et al, 2021). Multicomponent interventions consist of individualized and comprehensive assessment, home modifications, home visits, educational components to prevent falls and functional training for balance, strength and mobility (Stark et al, 2017a;Blaylock & Vogtle, 2017;Miranda-Duro et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, e-health system is defined as the digital or electronic healthcare products and services which increase the social independence and participation of elderly people relatively for health purposes [ 16 ]. The few researches that already have sought to investigate the reasons for using or not using technology have yielded somewhat contradictory results [ 17 ]. Although researchers revealed that older people have a positive attitude towards technology [ 5 , 18 ], hence they are less likely to use those technologies due to some barriers as compared to young adults [ 19 21 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…OT plays a key role in supporting older adults' participation in activities of daily living (ADL) such as bathing and dressing [13], instrumental activities of daily living (IADL) such as medication management and meal preparation [14], and home modifications to increase safety and prevent injury [15]. Although evidence for telerehabilitation is growing [9,[16][17][18][19][20], with video telehealth being used for exercise [21][22][23], recent reviews of telehealth OT highlight a paucity of evidence [24][25][26]. Furthermore, there are barriers to using technology for older adults, including low technical literacy [27] and some older adults' preference for telephone [28].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about how such diverse, complex OT interventions will be delivered using video telehealth, specifically to older adults, a population with distinct needs that may make participation in video telehealth more challenging because of decreased hearing, vision, and sensory processing; increased rates of cognitive impairment and reliance on family caregivers; as well as overall lower rates of technology literacy and use. Our own work providing home safety evaluations using video telehealth in dementia care highlighted numerous technological challenges, including inconsistent audio and visual signals [26].…”
Section: Introductionmentioning
confidence: 99%